Evaluation of a prompt card for community pharmacists performing consultations with patients on anticoagulation – lessons learned - Isabelle Arnet (Pharmacy Practice, 2018)
Objectives: To evaluate a prompt card (i.e., a post-card sized tool that lists counselling prompt information) with 5 key elements and 3 open key questions to ask patients in community pharmacies.Methods: Community pharmacists practicing in England and accredited to perform consultations used the prompt card during a formal consultation with emphasis on patients receiving oral anticoagulation. Main outcome measure was the number of performed consultations with pharmacists’ thoughts and feedbacks in writing.Results: During 8 weeks, 19 pharmacists (mean age: 36.6 (SD=9) years; 7 women; accredited an average of 12.9 (SD=9.8) years) performed 1,034 consultations and used the prompt card 104 times during anticoagulation consultations. Overall the prompt card was judged practical and relevant by the 16 pharmacists who used it (100%), especially because it outlines what a good consultation should comprise. The key elements offered a logical framework to guide the overall approach when undertaking a consultation. The two questions, “Why do you want to use this medicine?” and “Why would you not want to use this medicine?” generated negative responses from the patient and pharmacists, respectively.Conclusions: Our prompt card with key questions summarizing all the points that should be addressed in a consultation supported effective communication during patient-pharmacist interaction. Two questions need rephrasing and a further question is needed to determine how patients are using their medicines.